Social Responsibility Principles in Higher Education: Confessional Institutions Management Trends - Menegat, Jardelino (2018)
This article deals with social responsibility (SR) in Higher Education Institutions (HEIs) management, with a focus on confessional and non-profit private sector institutions. It aims to study the trends in the guiding principles within the SR, adopted in the higher education management by the Brazilian HEIs of La Salle University Network, a Christian religious education order, present  in 77 countries. A multiple case study was carried out, taking as reference the 5 HEIs maintained in Brazil by the Lasallian Brothers. The study analyzed the content of  the responses resulting from the application of a questionnaire to 66 university managers, who represent 57.4% of the total of managers, and conducted  a documentary analysis of the Institutional Development Plan (IDP) of each of the five Lasallian HEIs studied. The research reveals trends and specificities of university management, aggregated in four guiding principles: 1) ethical stance and actions transparency; 2) education and integral education; 3) institutional environment of reception, care and appreciation of the actors of educational action; and 4) commitment to life and the planet preservation.